Biomaterials for Guided Tissue Regeneration and Guided Bone Regeneration: A Review - Duarte, Nathália Dantas [UNESP]; Frigério, Paula Buzo [UNESP]; Chica, Gloria Estefania Amaya; Okamoto, Roberta [UNESP]; Buchaim, Rogério Leone; Buchaim, Daniela Vieira; Messora, Michel Reis; Issa, João Paulo Mardegan (MDPI, 2025)
This review aims to provide an overview of the types of membranes, bone substitutes, and mucosal substitutes used for GTR and GBR and briefly explores recent innovations for tissue regeneration and their future perspectives. Since this is a narrative review, no systematic search, meta-analysis, or statistical analysis was conducted. Using biomaterials for GTR and GBR provides a reduction in postoperative morbidity, as it contributes to less invasive clinical procedures, serving as an alternative to autogenous grafts. Moreover, randomized clinical trials (RCTs) and systematic reviews are essential for the evaluation of new biomaterials. These studies provide more robust evidence and help guide clinical practice in the selection of safer and more effective biomaterials, allowing for the personalization of treatment protocols for each patient.